Analyzing Optimization in Ship Routing for Indonesia's Liquified Natural Gas Logistics Network - Alwin Rizky; Dendi P. lshak (Green Publisher Indonesia, 2024)
This study focuses on optimizing the ship routing for Indonesia’s liquefied natural gas (LNG) logistics network using Mixed Integer Linear Programming (MILP). Indonesia's pivotal role in the global LNG market underscores the need for efficient logistics, especially given the challenges of limited port capacity, infrastructure, fluctuating demand, and environmental impact. MILP techniques were applied to address these challenges by optimizing vessel routes, minimizing costs, and reducing emissions. The research identified bottlenecks within Indonesia's logistics network and proposed optimized shipping strategies that enhance cost-effectiveness and operational efficiency. The findings contribute to sustainable energy logistics and provide actionable insights for stakeholders managing Indonesia's LNG supply chain.